An Inducible Fluorescent Reporter System to Measure Lux Operon Promoter Activity - (:unkn) unknown (My University, 2017)
Bioluminescence is the enzymatic production of light by a living organism. Many species of marine bacteria produce light with varying degrees of brightness. The lux operon is responsible for bioluminescence and is well studied, however it is currently unknown why different species of bacteria display different brightness levels. A dual-plasmid system designed to mimic the quorum-sensing induction of the lux operon was created and successfully implemented in E. coli. This was accomplished through the use of an arabinose-inducible plasmid containing a luxR gene from Vibrio harveyi, and then using the resulting LuxR protein to activate the lux promoter in a second plasmid. The second plasmid was created using a new vector containing a fluorescent reporter. An upstream region from a Vibrio species containing a promoter for the lux operon could then be inserted into the plasmid vector and induced using the previously made LuxR plasmid. The fluorescence and luminescence levels of different strains were compared in the hopes to better understand the impact of promoter activity on light production.